Psychometric Properties of the Zarit Burden Interview in Informal Caregivers of Persons With Intellectual Disabilities - Boluarte-Carbajal, Alicia; Paredes-Angeles, Rubí; Tafur-Mendoza, Arnold Alejandro (Frontiers in Psychology, 2022)
Intellectual disability leads to a loss of autonomy and a high level of dependence, requiring support from another person permanently. Therefore, it is necessary to incorporate the assessment of caregiver burden in healthcare actions, to avoid putting the health of caregivers and patients at risk. In this sense, the study aimed to analyze the internal structure of the Zarit Burden Interview (ZBI) in a sample of caregivers of people with intellectual disabilities, to provide convergent and discriminant evidence with a measure of the risk of maltreatment, and to estimate the reliability of the scores from the Classical Test Theory and the Rasch Measurement Theory. The study was instrumental. The sample consisted of 287 Peruvian informal primary caregivers of persons diagnosed with intellectual disabilities. To collect validity evidence, the internal structure (confirmatory factor analysis, CFA) and the relationship with other variables (convergent and discriminant evidence) were used, while reliability was estimated through the omega coefficient and Rasch analysis. The internal structure of the ZBI corroborated a unidimensional structure. In terms of convergent and discriminant evidence, the scale presents adequate evidence. Reliability levels were also good. Previously, the psychometric properties of the ZBI have not been studied in caregivers of people with intellectual disabilities, and it represents the first study of the scale in Peru. The results obtained will allow the use of this scale to design actions in the work with caregivers and studies to understand the psychology of the caregiver.